Tragiczna historia literatury – projekt (nie)szczęśliwy? Wokół koncepcji Waltera Muschga - Wycykał, Monika (Śląskie Studia Polonistyczne, 2014)
The article is an attempt to find a formula, which would allow to look at the “history of literature” category through a new perspective – based on incongruence of current paradigms with challenges of modern literature science. The author, while not undermining the hitherto achievements in this area, attempts to show that it is still possible to construct a positive project, which would allow to describe the history of literature. In order to do so, she presents the works of Walter Muschg, a German-speaking researcher, especially his epochal Tragische Literaturgeschichte, in order to deliberate on the possibility of using the “tragedy” category in works on history of literature by replacing the widespread chronological order with a spiritual one, which would function above history.